2011
DOI: 10.1007/s10611-011-9332-3
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking? Exploring the relevance of the notion of human trafficking to describe the lived experience of sex workers in Cape Town, South Africa

Abstract: This article reports on the findings of a study of the sex work industry in Cape Town that was undertaken by the Institute for Security Studies (ISS) and the Sex Worker Education and Advocacy Taskforce (SWEAT) between 2006 and 2008. The study employed qualitative and quantitative methods to gather data about inter alia, the size of the sex work industry in Cape Town, working conditions in the industry, recruitment practices, factors that resulted in women working in the industry, and the extent of human traffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 3 publications
2
19
0
Order By: Relevance
“…A study of FSWs in Soweto, South Africa, showed that 53.8 and 55.6% had experienced intimate partner and non-intimate partner sexual violence in their lifetime (respectively). In Johannesburg, 20% of FSWs reported experiencing sexual violence, while 54% reported any physical violence in the past year [1,6]. Globally, violence is associated with inconsistent condom usage, sexually transmitted infection (STI) and HIV acquisition, undermining economic capital, and it has a widespread social impact [711].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study of FSWs in Soweto, South Africa, showed that 53.8 and 55.6% had experienced intimate partner and non-intimate partner sexual violence in their lifetime (respectively). In Johannesburg, 20% of FSWs reported experiencing sexual violence, while 54% reported any physical violence in the past year [1,6]. Globally, violence is associated with inconsistent condom usage, sexually transmitted infection (STI) and HIV acquisition, undermining economic capital, and it has a widespread social impact [711].…”
Section: Introductionmentioning
confidence: 99%
“…These factors then result in perceived transgressions being punished through violence. SWs are not considered to have the right to give consent or to choose who they sell sex to, by clients, managers, police, and healthcare officials alike [6]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these issues have been documented in a small but growing body of research on sex work in South Africa (see, for example, Walker and Oliviera 2015;Richter et al 2012;Gould 2011;Vearey et al 2011;Gould and Fick 2008;Stadler and Delany 2006). These in turn fit with a larger global picture of the vulnerabilities and risks faced by women selling sex, particularly in criminalised contexts (see, for example, Global Commission on HIV and the Law 2012 ;Weitzer 2010;Agustín 2007;Kempadoo 2005;Sanders 2005;Busza 2004).…”
Section: Introductionmentioning
confidence: 99%